Capsaicin, a TRPV1 Ligand, Suppresses Bone Resorption by Inhibiting the Prostaglandin E Production of Osteoblasts, and Attenuates the Inflammatory Bone Loss Induced by Lipopolysaccharide. (3rd April 2012) - Kobayashi, Megumi; Watanabe, Kenta; Yokoyama, Satoshi; Matsumoto, Chiho; Hirata, Michiko; Tominari, Tsukasa; Inada, Masaki; Miyaura, Chisato
Abstract : Capsaicin, a transient receptor potential vanilloid type 1 (TRPV1) ligand, regulates nerve-related pain-sensitive signals, inflammation, and cancer growth. Capsaicin suppresses interleukin-1-induced osteoclast differentiation, but its roles in bone tissues and bone diseases are not known. This study examined the effects of capsaicin on inflammatory bone resorption and prostaglandin E (PGE) production induced by lipopolysaccharide (LPS) in vitro and on bone mass in LPS-treated mice in vivo . Capsaicin suppressed osteoclast formation, bone resorption, and PGE production induced by LPS in vitro . Capsaicin suppressed the expression of cyclooxygenase-2 (COX-2) and membrane-bound PGE synthase-1 (mPGES-1) mRNAs and PGE production induced by LPS in osteoblasts. Capsaicin may suppress PGE production by inhibiting the expression of COX-2 and mPGES-1 in osteoblasts and LPS-induced bone resorption by TRPV1 signals because osteoblasts express TRPV1. LPS treatment markedly induced bone loss in the femur in mice, and capsaicin significantly restored the inflammatory bone loss induced by LPS in mice. TRPV1 ligands like capsaicin may therefore be potentially useful as clinical drugs targeting bone diseases associated with inflammatory bone resorption.